Novel rRNA transcriptional activity of NhaR revealed by its growth recovery for the bipA-deleted Escherichia coli at low temperature - Choi, Eunsil; Huh, Ahhyun; Hwang, Jihwan (Frontiers in Molecular Biosciences, 2023)
The BipA protein is a universally conserved GTPase in bacterial species and is structurally similar to translational GTPases. Despite its wide distribution, BipA is dispensable for growth under optimal growth conditions but is required under stress conditions. In particular, bipA-deleted cells (ESC19) have been shown to display a variety of phenotypic changes in ribosome assembly, capsule production, lipopolysaccharide (LPS) synthesis, biofilm formation, and motility at low temperature, suggesting its global regulatory roles in cold adaptation. Here, through genomic library screening, we found a suppressor clone containing nhaR, which encodes a Na+-responsive LysR-type transcriptional regulator and whose gene product partially restored the growth of strain ESC19 at 20°C. The suppressed cells showed slightly reduced capsule production and improved biofilm-forming ability at 20°C, whereas the defects in the LPS core and swimming motility were not restored but aggravated by overexpression of nhaR. Notably, the overexpression partially alleviated the defects in 50S ribosomal subunit assembly and rRNA processing of ESC19 cells by enhancing the overall transcription of rRNA. Electrophoretic mobility shift assay revealed the association of NhaR with the promoter of seven rrn operons, suggesting that NhaR directly regulates rRNA transcription in ESC19 at 20°C. The suppressive effects of NhaR on ribosomes, capsules, and LPS were dependent on its DNA-binding activity, implying that NhaR might be a transcriptional factor involved in regulating these genes at 20°C. Furthermore, we found that BipA may be involved in adaptation to salt stress, designating BipA as a global stress-responsive regulator, as the deletion of bipA led to growth defects at 37°C and high Na+ concentrations without ribosomal defects.